MRI‐Based Iron Phenotyping and Patient Selection for Next‐Generation Sequencing of Non–Homeostatic Iron Regulator Hemochromatosis Genes. Issue 5 (13th July 2021) - Viveiros, André; Schaefer, Benedikt; Panzer, Marlene; Henninger, Benjamin; Plaikner, Michaela; Kremser, Christian; Franke, André; Franzenburg, Sören; Hoeppner, Marc P.; Stauder, Reinhard; Janecke, Andreas; Tilg, Herbert; et al.
Abstract : Background and Aims: High serum ferritin is frequent among patients with chronic liver disease and commonly associated with hepatic iron overload. Genetic causes of high liver iron include homozygosity for the p.Cys282Tyr variant in homeostatic iron regulator ( HFE ) and rare variants in non‐HFE genes. The aims of the present study were to describe the landscape and frequency of mutations in hemochromatosis genes and determine whether patient selection by noninvasive hepatic iron quantification using MRI improves the diagnostic yield of next‐generation sequencing (NGS) in patients with hyperferritinemia. Approach and Results: A cohort of 410 unselected liver clinic patients with high serum ferritin (defined as ≥200 μg/L for women and ≥300 μg/L for men) was investigated by HFE genotyping and abdominal MRI R2*. Forty‐one (10%) patients were homozygous for the p.Cys282Tyr variant in HFE . Of the remaining 369 patients, 256 (69%) had high transferrin saturation (TSAT; ≥45%) and 199 (53%) had confirmed hepatic iron overload (liver R2* ≥70 s −1 ). NGS of hemochromatosis genes was carried out in 180 patients with hepatic iron overload, and likely pathogenic variants were identified in 68 of 180 (38%) patients, mainly in HFE (79%), ceruloplasmin (25%), and transferrin receptor 2 (19%). Low spleen iron (R2* <50 s −1 ), but not TSAT, was significantly associated with the presence of mutations. In 167 patients (93%), no monogenic cause of hepatic iron overload could be identified. Conclusions: In patients without homozygosity for p.Cys282Tyr, coincident pathogenic variants in HFE and non‐HFE genes could explain hyperferritinemia with hepatic iron overload in a subset of patients. Unlike HFE hemochromatosis, this type of polygenic hepatic iron overload presents with variable TSAT. High ferritin in blood is an indicator of the iron storage disease, hemochromatosis. A simple genetic test establishes this diagnosis in the majority of patients affected. MRI of the abdomen can guide further genetic testing.